Co-pyrolysis of furniture wood with mixed plastics and waste tyres: assessment of synergistic effect on biofuel yield and product characterization under different blend ratio - Kumar, Indradeep; Tirlangi, Satyanarayana; Kathiresan, K.; Sharma, Vipin; Madhu, P.; Sathish, T.; Agbulut, Umit; Murugan, P. (NATURE PORTFOLIO, 2024)
Pyrolysis of waste furniture wood, mixed plastics and waste tyres was examined separately and in different combinations from the perspective of improved value products and energy production. The effect of different combinations of furniture wood, plastics and tyres on the product distribution during co-pyrolysis was analyzed. The experimental work throughout this study was performed at a temperature of 500 degrees C. Prior to the pyrolysis experiments, thermogravimetric analysis was done to assess the thermal degradation behavior of all selected feedstocks. During individual pyrolysis, mixed plastic wastes produced 70.6 wt% of pyrolysis liquid, which is 37.9% and 33.4% more than furniture wood and waste tyres. During co-pyrolysis, a binary blend of mixed plastics and waste tyres produced 63.3 wt% of pyrolysis liquid, which is 7.65% more than the logarithmic mean value, indicating a positive synergistic interaction on liquid production. The liquid yield of the ternary blend was observed to be as low as 54.4 wt% due to the lower volatiles present in the blend. The presence of volatiles in the feedstock is correlated with the production of liquids by individual and co-pyrolysis. For feed-flexible, more efficient, and cleaner operating systems, the increased liquid production offers crucial information. With the use of Fourier transform infrared spectroscopy (FT-IR) and gas chromatography/mass spectroscopy (GC-MS), the impact of different combinations on product characterization was investigated. The characterization study of the pyrolysis liquid obtained from mixed plastics showed the presence of different aromatic and aliphatic compounds. The findings offered viable options for efficiently utilizing waste materials, particularly plastics and tyres to improve the quality and substance of products.
Keywords: Co-pyrolysis; Binary and ternary blends; Synergistic effect; Characterization; THERMOCHEMICAL BEHAVIORS; FLASH PYROLYSIS; TYRE PYROLYSIS; OIL; BIOMASS; KINETICS; RECOVERY; SAWDUST; QUALITY; REACTOR; Science & Technology - Other Topics